Green Building Assessment of Cilacap State Polytechnic: Building A - Vicky Prasetia; Theresia Evila Purwanti Sri Rahayu; Roy Aries Permana Tarigan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Buildings to achieve sustainable development must meet environmental criteria. This environmentally friendly building design is often referred to as a green building. The Green Building concept aims to reduce the negative impact on the environment from the construction and utilization of buildings. This study will discuss the criteria and requirements that must be met by company buildings to be categorized as Green Buildings according to the Green Building Council Indonesia (GBCI) and obtain a Greenship certificate, as well as any components at the construction and maintenance stage that affect the fulfillment of these requirements. This study uses a quantitative method by the green ship standard version 1.1. The greens criteria assessment in Building A resulted in 51 points. The results of this assessment explain that Building A is included in the silver category. This result explains that 44% of Building A's facilities have met the green building criteria. Upgrading from silver to gold category needs to increase 7 points by adding facilities, standard operating procedures, and policies.